2020
DOI: 10.1021/acs.cgd.0c00562
|View full text |Cite
|
Sign up to set email alerts
|

Experimental, Structural, and Computational Investigation of Mixed Metal–Organic Frameworks from Regioisomeric Ligands for Porosity Control

Abstract: Porosity control and structural analysis of metal–organic frameworks (MOFs) can be achieved using regioisomeric ligand mixtures. While ortho-dimethoxy-functionalized MOFs yielded highly porous structures and para-dimethoxy-functionalized MOFs displayed almost nonporous properties in their N2 isotherms after evacuation, regioisomeric ligand-mixed MOFs showed variable N2 uptake amount and surface area depending on the ligand-mixing ratio. The quantity of N2 absorbed was tuned between 20 and 300 cm3/g by adjustin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…1,2 In the recent decade, CPs containing more than one metal have attracted significant research interest, as they can exhibit completely different structures and properties than their homometallic analogs, offering new reaction patterns and novel fields of application. [3][4][5][6][7][8] Since the metal-ligand connectivity in these compounds is often difficult to predict and to control, the development of rational synthetic strategies is of fundamental importance. In recent contributions, we have shown that dithiocarbamate-functionalized carboxylates (DTCCs) can coordinate selectively to a to a soft (thiophilic) and a hard (oxophilic) metal center at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In the recent decade, CPs containing more than one metal have attracted significant research interest, as they can exhibit completely different structures and properties than their homometallic analogs, offering new reaction patterns and novel fields of application. [3][4][5][6][7][8] Since the metal-ligand connectivity in these compounds is often difficult to predict and to control, the development of rational synthetic strategies is of fundamental importance. In recent contributions, we have shown that dithiocarbamate-functionalized carboxylates (DTCCs) can coordinate selectively to a to a soft (thiophilic) and a hard (oxophilic) metal center at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our recent contribution to MOFs with regioisomerism of multiple functional groups, [18][19][20][21][22] a dual-functionalized benzene-1,4-dicarboxylic acid (BDC) ligand with two reactivechemical handles, viz. NH 2 and OH, was designed for cyclization on MOFs (Scheme S1 in ESI †).…”
mentioning
confidence: 99%